Comparing the effectiveness of propranolol versus atenolol in inducing clinical clearance in the treatment of infantile haemangioma: A randomised controlled trial - Raihan Ashraf; Rahul Mahajan; Muneer A Malik; Sanjeev Handa; Anindita Sinha; Dipankar De; Naresh Sachdeva (Wolters Kluwer Medknow Publications, 2023)
Background: Despite the excellent clinical efficacy of oral propranolol in the management of infantile haemangiomas (IHs), there is a need to further evaluate other beta blockers that may be equally efficacious but result in lesser adverse effects. We compared the efficacy and short-term safety of atenolol, a hydrophilic cardio-selective beta blocker, with propranolol, in the treatment of IHs. Materials and Methods: Sixty patients with complicated and/or cosmetically significant IHs were randomised into two groups, oral propranolol group (2 mg/kg/day) and the oral atenolol (1 mg/kg/day) group, respectively, for 9 months. Patients were assessed clinically, by the use of Doppler ultrasonography (USG) and measurement of serum hypoxia-inducible factor 1 alpha (HIF-1α). Results: Twenty-two of 30 patients achieved complete clearance in the propranolol group (0.73; 95% CI = 0.54 to 0.87) compared with 13 of 25 patients in the atenolol group (0.52; 95% CI = 0.31 to 0.72). The mean time to achieve Physician Global Assessment Score 5 (PGA5) (25.00 ± 8.87 weeks) was significantly lesser in the propranolol group versus the atenolol group (31.69 ± 7.01 weeks; log-rank = 0.04). The two groups were comparable in terms of adverse effect profile, degree of volume reduction in USG and reduction in HIF-1α levels. Conclusions: Propranolol (2 mg/kg/day) is better than atenolol (1 mg/kg/day) in inducing complete clinical clearance of IH although the results need to be reproduced in larger studies. ClinicalTrials.gov Identifier: NCT03237637